ASMT gene expression correlates with cognitive impairment in patients with recurrent depressive disorder - Talarowska, Monika; Szemraj, Janusz; Zajączkowska, Marlena; Gałecki, Piotr (Medical science monitor, 2014)
Recurrent depressive disorder is a multifactorial disease; one of the typical features is cognitive impairment. The purpose of this study was analysis of ASMT gene expression both on mRNA and protein levels in patients with recurrent depressive disorder (rDD) and assessment of the relationship between plasma level of ASMT protein, gene expression on mRNA level, and cognitive performance. The study included 236 subjects: patients with rDD (n=131) and healthy subjects (n=105, CG). Cognitive function assessment was based on: Trail Making Test, The Stroop Test, Verbal Fluency Test (VFT), and Auditory Verbal Learning Test (AVLT). Both mRNA and protein expression levels of ASMT gene were significantly higher in healthy subjects when compared to rDD. The average ASMT mRNA expression level measured for the entire group was M=0.21 (SD=0.09), and the protein level was M=12.84 (SD=3.29). In patients with rDD, statistically significant correlations occurred between both mRNA and protein expression levels and part A of the TMT (negative correlation) and verbal fluency test (positive correlation). In the group CG, there was no statistically significant association between the analyzed variables. In the entire group there was a statistically significant correlation between both ASMT mRNA and protein expression levels and all the neuropsychological tests used in the survey. 1. Our study confirms previous results showing decreased mRNA and protein expression levels of ASMT gene in depression. 2. Our data suggest a relationship between decreased mRNA and protein expression levels of ASMT gene and cognitive impairment.